Assessing the Current Status and Proposing Solutions for Heavy Metal Management in the Saigon River Basin Sediments - Tong, Nguyen Xuan; Thi Bich Van, Pham; Hung Anh, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 2, 2023)
The sediment is the final environment where heavy metals accumulate and directly impact the health of aquatic systems and humans.Therefore, t he study was carried out to determine the total content and forms of heavy metals in the sediments at 13 locations in the Saigon River basin in rain and dry seasons of 2022. In addition, this research also assesses the pollution risk level and the correlation between heavy metals and physicochemical properties in the sediments. Chemical analysis was applied to determine the contributors of heavy metals while the geochemical calculation methods (hazard quotient (HQ), geo-accumulation index (I geo ), pollutant load index (PLI), individual contamination factors (ICF) and global contamination factors (GCF), risk assessment code (RAC)) were used to assess the pollution risk level in river sediments. The results show that Ag, Ba, Mn and Zn were metals with high pollution risks, especially in rain season. The results showed that the total concentration of heavy metals in sediments in rain season ranges from 109.92 to 4591.01 mg.kg –1 (Mn > Zn > Li > Ba > Ag > Cr > Cu > Pb) and in dry season from 0 to 3117.8 mg.kg –1 (Mn > Ag > Zn > Li > Ba > Cr > Cu > Pb). Applying the sequential extraction method, the metal forms of Ba, Cr, Cu and Li in the sediment samples are mainly residues (F5) (up to 76.53%), proving these elements dominated by natural sources. In contrast, the Mn extract composition was strongly influenced by human activity with exchange (F1) (>50%) and carbonate (F2) (>20%) components predominating. For Ag, Pb and Cu were mainly in organic form (F4). In dry season, the river sediments didn’t contain Pb because it didn’t carry away rainwater. In particular, Zn had a strong fluctuation between the extracted forms in rain and dry seasons, showing impacts from nature and humans sources. Besides, the statistical analysis results showed that pH affected Cu and Zn contents with a negative correlation, but did not detect the correlation between heavy metals and sand, clay, electrical conductivity (EC) in Saigon river sediments. The research results are foundational for the implementation and design of effective remediation strategies to prevent risks of river sediments degradation in the future.